Exploration of Entrepreneurial Attitudes: A Comparison Between Indigenous and Chinese Ethnicity - Hikmah Rahmah; Apriani Riyanti; Merry Lapasau; Sulis Setiawati; Syukrio Idaman (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2023)
This research is a comparational study that aims to determine the differences in entrepreneurial attitudes between ethnic Chinese entrepreneurs and ethnic Indigenous entrepreneurs in Mamajang District and Wajo District, Makassar city. This research is quantitative research. The population in this study were ethnic Chinese entrepreneurs and ethnic Indigenous entrepreneurs in Mamajang and Wajo sub-districts, with a research sample of 60 entrepreneurs divided into two, namely 30 entrepreneurs from Chinese ethnicity and 30 entrepreneurs from Indigenous ethnicity. The sampling technique used was snowball sampling. The data analysis method in this study uses the t-test. The results of the difference test using the t-test technique obtained a value of t = 3.481 with a significance value or p = 0.001. These results indicate that there are differences in entrepreneurial attitudes between ethnic Chinese and indigenous ethnicities in mamajang subdistrict and wajo sub-district of Makassar city. The results showed that ethnic Chinese entrepreneurs have a higher entrepreneurial attitude than ethnic indigenous entrepreneurs. Testing on each aspect found a difference in the aspects of discipline and independence with ethnic Chinese having a higher score than ethnic natives while in the aspects of high commitment, honesty, creative and innovative and realistic found no difference.